Introgression of the Aegilops speltoides Su1-Ph1 Suppressor into Wheat - Li, Hao; Deal, Karin R.; Luo, Ming-Cheng; Ji, Wanquan; Distelfeld, Assaf; Dvorak, Jan (Frontiers in Plant Science, 2017)
Meiotic pairing between homoeologous chromosomes in polyploid wheat is inhibited by the Ph1 locus on the long arm of chromosome 5 in the B genome. Aegilops speltoides (genomes SS), the closest relative of the progenitor of the wheat B genome, is polymorphic for genetic suppression of Ph1. Using this polymorphism, two major suppressor loci, Su1-Ph1 and Su2-Ph1, have been mapped in Ae. speltoides. Su1-Ph1 is located in the distal, high-recombination region of the long arm of the Ae. speltoides chromosome 3S. Its location and tight linkage to marker Xpsr1205-3S makes Su1-Ph1 a suitable target for introgression into wheat. Xpsr1205-3S was introgressed into hexaploid bread wheat cv Chinese Spring (CS) and from there into tetraploid durum wheat cv Langdon (LDN). Sequential fluorescence in situ hybridization and genomic in situ hybridization showed that an Ae. speltoides segment with Xpsr1205-3S replaced the distal end of the long arm of chromosome 3A. In the CS genetic background, the chromosome induced homoeologous chromosome pairing in interspecific hybrids with Ae. peregrina but not in progenies from crosses involving alien disomic substitution lines. In the LDN genetic background, the chromosome induced homoeologous chromosome pairing in both interspecific hybrids and progenies from crosses involving alien disomic substitution lines. We conclude that the recombined chromosome harbors Su1-Ph1 but its expression requires expression of complementary gene that is present in LDN but absent in CS. We suggest that it is unlikely that Su1-Ph1 and ZIP4-1, a paralogue of Ph1 located on wheat chromosomes 3A and 3B and Ae. tauschii chromosome 3D, are equivalent. The utility of Su1-Ph1 for induction of recombination between homoeologous chromosomes in wheat is illustrated.